Understanding US â€œRe-pivotâ€ to Asia - Sigit, Muhammad (Indonesian Journal of Peace and Security Studies (IJPSS), 2020)
This paper explains the nature and the context of the future of US foreign policy to the Asia or so-called US re-pivot policy to Asia. By using the historical method, this paper tries to make sense of US continuous engagement in Asia, past and present; with a hope to illuminate even quite distant futures of US foreign policy direction. The 2020 US presidential candidates, Donald Trump and Joe Biden have signaled their strong intention of US re-pivot to Asia. However, the new re-pivot to Asia should be different from Obama’s ‘pivot to Asia’. Re-pivot should bring practical economic, strategic, and political benefits to Asian countries, rather than simply containing China.